2014
DOI: 10.1002/2013jd020971
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a nitrous acid (HONO) reservoir at the ground surface in Bakersfield, CA, during CalNex 2010

Abstract: Measurements of HONO (g) were validated to be free of known interferences for wet chemical instrumentation. The accumulation of nitrite into particulate matter was found to be enhanced when gaseous mixing ratios of HONO (g) were highest. Reactive uptake of HONO (g) on to lofted dust and the ground surface, forming a reservoir, is a potential mechanism to explain these observations. The AIM-IC HONO (g) measurements were parameterized in a chemical model to calculate the ground surface daytime HONO (g) source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 100 publications
3
62
1
Order By: Relevance
“…However, our results seem to indicate that both photolysis of surface HNO 3 / nitrate and photo-enhanced NO 2 conversion are likely active. Acid displacement of HONO deposited during the night, as proposed by VandenBoer et al (2014), can contribute to the observed HONO flux, but a calculation of the total deposited HONO throughout the night with the integrated daytime flux reveals that this mechanism by itself cannot explain the observed daytime HONO formation. The low temperatures and alkaline soil make the bacterial production of nitrite and its release (Su et al, 2011) likely unimportant.…”
Section: Discussionmentioning
confidence: 97%
“…However, our results seem to indicate that both photolysis of surface HNO 3 / nitrate and photo-enhanced NO 2 conversion are likely active. Acid displacement of HONO deposited during the night, as proposed by VandenBoer et al (2014), can contribute to the observed HONO flux, but a calculation of the total deposited HONO throughout the night with the integrated daytime flux reveals that this mechanism by itself cannot explain the observed daytime HONO formation. The low temperatures and alkaline soil make the bacterial production of nitrite and its release (Su et al, 2011) likely unimportant.…”
Section: Discussionmentioning
confidence: 97%
“…Despite specifying a 'lower-limit' value, this investigation may be effectively considering the high end of contribution of soil bacteria to HONO because "optimum" values of flux are used for both soil types. Source S3 is the re-emission of HONO from a surface nitrite reservoir by displacement from HNO 3 and HCl, as in VandenBoer et al (2014VandenBoer et al ( , 2015 and shown in Eq. (6):…”
Section: Parameterization and Evaluation Of Newly Identified Hono Soumentioning
confidence: 99%
“…, and h is the displacement efficiency, ranging from 1% to 9% to 20% for 'lowerlimit', 'likely', and 'upper-limit' values, respectively (VandenBoer et al, 2014). This parameterization was constrained by the calculation of a 'reservoir' of nitrite from deposited HONO, approximated from a material balance on the ground where the source of nitrite is mechanism L1 and loss is due to displacement from mechanism S3.…”
mentioning
confidence: 99%
“…The contributions of O 3 and H 2 CO were 34 and 26 %, respectively. Noontime HONO concentrations during CalNex-SJV were between 30 and 250 ppt (Ren et al, 2011;VandenBoer et al, 2013) making HONO an important daytime radical source (32 %). H 2 O 2 photolysis (1 %) and O 3 + alkene reactions (7 %) are less important to the daytime total.…”
Section: S E Pusede Et Al: Temperature-dependent Impacts Of Emissimentioning
confidence: 99%